Uncertainty quantification of modal parameter estimates obtained from subspace identification: An experimental validation on a laboratory test of a large-scale wind turbine blade. (1st April 2022) - Greś, Szymon; Riva, Riccardo; Süleyman, Cem Yeniceli; Andersen, Palle; Łuczak, Marcin Mieczyslaw
Abstract: The uncertainty afflicting modal parameter estimates stems from e.g., the finite data length, unknown, or partly measured inputs and the choice of the identification algorithm. Quantification of the related errors with the statistical Delta method is a recent tool, useful in many modern modal analysis applications e.g., damage diagnosis, reliability analysis, model calibration. In this paper, the Delta method-based uncertainty quantification methodology is validated for obtaining the uncertainty of the modal parameter and the modal indicator estimates in the context of several well-known subspace identification algorithms. The focus of this study is to validate the quality of each Delta method-based approximation with respect to the experimental Monte Carlo distributions of parameter estimates using a statistical distance measure. On top of that, the accuracy in obtaining the related confidence intervals is empirically assessed. The case study is based on data obtained from an extensive experimental campaign of a large scale wind turbine blade tested in a laboratory environment. The results confirm that the Delta method is, on average, adequate to characterize the distribution of the considered estimates solely based on the quantities obtained from one data set, validating the use of this statistical framework for uncertainty quantification in practice. Highlights: Modal parameters and modal indicators are estimated from data of a wind turbine blade. Their estimates are afflicted with statistical uncertainty, which is quantified with Delta method. The distribution of modal parameter estimates is Gaussian. A special case of MAC and MPC estimates is characterized by a scaled and shifted chi2 distribution. The quality of Delta method approximations is validated with the experimental Monte Carlo distributions.